(untitled) (Journal of Nepal Physical Society, 2017)
Materials with perovskite crystal structure represent an interesting class of materials which, due to their simple structures and unique electronic and dielectric properties, has a great potential for applications in various technological fields, such as mechanical, electro-optic and semiconducting. We perform calculation of density of states (DOS) and band structures for fluoride perovskite like RbMgF3 using the full potential linearized augmented plane wave (FP-LAPW) method. To calculate the electronic properties, the exchange-correlation potential has been applied by using the generalized gradient approximation (GGA). From the calculation the lattice parameter of RbMgF3 found to be 4.139 Å. The band gap of RbMgF3 through the electron energy bands by GGA is obtained as 7.6 eV showing insulating behavior which is in good agreement with the available experimental data as well as previously calculated results. Journal of Nepal Physical Society Volume 4, Issue 1, February 2017, Page: 23-26